Language Festival as a CLIL-Based Learning Model: Enhancing Arabic Proficiency in Islamic Boarding School Context - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Siti Nikmatul Rochma; Nuraeni Rahmawati (Jurnal Penelitian Pendidikan, 2026)
This study investigates the implementation of a Language Festival as a Content and Language Integrated Learning (CLIL)-based model in enhancing Arabic proficiency within an Islamic boarding school context. Conducted at the female campus of Pondok Modern Darussalam Gontor during its 100th anniversary celebration, this research employs a qualitative case study design involving students, teachers, and festival organizers. Data were collected through participant observation, semi-structured interviews, and document analysis, and analyzed using thematic analysis. The findings reveal that the Language Festival functions as an authentic learning environment that significantly improves students’ Arabic communicative competence, particularly in speaking fluency, vocabulary development, and confidence. In addition, the model fosters learners’ motivation, engagement, and higher-order thinking skills through integrated content-based activities such as speeches, debates, and drama. The study also highlights the importance of contextual factors, including institutional culture and immersive language environment, in determining the effectiveness of CLIL implementation. However, challenges remain in balancing language and content integration, as well as in addressing variations in students’ proficiency levels. This study contributes to the growing body of CLIL research by proposing a festival-based learning model that is contextually relevant and pedagogically innovative for Islamic education. The findings offer both theoretical and practical implications for the development of integrated language learning approaches in similar educational settings.